Productive and reproductive performance of cattle in the tropical part of India - C, SUMI PRINCESS; KUMAR, DINESH; SARAN, SANDEEP; KUMAR, SANJAY; SHARMA, RUCHI; JUNIWAL, CHITRA; P, THAMIZHAN; NISHANTH J, MARIA ANTO DANI; D, DINESH (The Indian Journal of Animal Sciences, 2024)
The assessment of productive and reproductive traits helps in identifying animals with superior germplasm in comparison to their population mean which helps in selecting animals for breeding purposes. The early detection of low- performing animals based on the parameters considered for the evaluation of productive and reproductive traits in the study can help in culling animals at an early age, thus saving the cost of maintenance or losses for dairy farmers. Overall, it was observed that the productive and reproductive performance of cross-bred cows was better as compared to the buffaloes and non-descript cows. Therefore, the study advises taking the following steps; record keeping, regular testing for various diseases, balanced ration, maintenance of proper hygiene, availability of nearby veterinary services, and upgradation of non- descript animals to exploit maximum production potential at farmers’ level.